The Influence of Brand Luxury, Customer Experience, and E-Wom on Purchasing Decisions - Nurjihan, Syifa Rahmawati; Bertuah, Eka (Social Science Academic, 2023)
The aims of the study is to examine and analyze the influence of luxury brands, customer experience, e-wom, partially or simultaneously on the purchase decision of Apple products, and to determine the most dominant variables in influencing purchasing decisions. The study used quantitative methods with sample respondents who were buyers of Apple products and used Apple products, operating inside or outside Jakarta, Bogor, Depok, Tangerang and Bekasi. The questionnaire collected 170 respondents, the data was then processed by multiple linear regression. Based on the results of the analysis, it is known that the variables of brand luxury, customer experience, and e-wom simultaneously have a positive and significant influence on purchasing decisions on Apple products. Partially, the variables of brand luxury, customer experience, and e-wom have proven to have a positive and significant influence on purchasing decisions on Apple products. Then in the results of the analysis, the e-wom variable is the most dominant variable